Board Attributes and Banks’ Abnormal Loan Loss Provision - Hussaini Bala; Anas Abdulwahab; Hassan Bala; Umar Sani Bebeji (STIM LASHARAN JAYA MAKASSAR, 2023)
It is pertinent to the document that BOD has the responsibility to scrutinize the information enclosed financial statements to ensure a quality and reliable financial information. More so, this paper examined the correlation between board attributes and loan loss provision of sampled Nigerian banks. This research covers a ten years period (2012-2021). Information related to data was got from the sampled banks’ yearly information. Paris-winsten regression, heteroskedastic panel corrected standard error (PCSE) was used because the data is homoskedastic in nature. This study introduced the whistle blowing policy as a control variable. Again, this study introduced learning by theory to explain firm age (control variable). Findings in the results show a significant positive correlation between board size and abnormal loan loss provision (ABLLP). Board meetings may have a negative insignificant connection with ABLLP. While, board autonomy has a positive insignificant correlation with ABLLP. Finally, it was found that whistleblowing may not significantly prevent the practice of ABLLP by banks in Nigeria. As a result, this study established that authorities like the Nigerian Apex Bank should ensure the compliance of their codes of best practice which will serve as an avenue to achieve a financial reporting quality. Federal Republic of Nigeria should ensure the full implementation of the law on whistleblowing policy and protection of whistleblowers. Furthermore, all findings and recommendations are restricted to the DMBs in Nigeria. Lastly, studies in the future are advised to focus on board attributes in the other domains where there is a practical problem to be addressed.